HISTORY OF FORCEPS - A. K. Blbulyan (Акушерство, гинекология и репродукция)
The invention of forceps was of great importance for practical obstetrics, however, the invention Chamberlains was kept secret for a long time, while the others approached them step by step. In addition to practical importance, the story with forceps carries a great human lesson. A lesson for generations.